On the line: slaughterhouse lives and the making of the new south - Ribas, Vanesa (University of California Press, 2015)
"How does one put into words the rage that workers feel when supervisors threaten to replace them with workers who will not go to the bathroom in the course of a fourteen-hour day of hard labor, even if it means wetting themselves on the line?"-From the PrefaceIn this gutsy, eye-opening examination of the lives of workers in the New South, Vanesa Ribas, working alongside mostly Latino/a and native-born African American laborers for sixteen months, takes us inside the contemporary American slaughterhouse. Ribas, a native Spanish speaker, occupies an insider/outsider status there, enabling her to capture vividly the oppressive exploitation experienced by her fellow workers. She showcases the particular vulnerabilities faced by immigrant workers-a constant looming threat of deportation, reluctance to seek medical attention, and family separation-as she also illuminates how workers find connection and moments of pleasure during their grueling shifts. Bringing to the fore the words, ideas, and struggles of the workers themselves,On The Lineunderlines how deep racial tensions permeate the factory, as an overwhelmingly minority workforce is subject to white dominance. Compulsively readable, this extraordinary ethnography makes a powerful case for greater labor protection, especially for our nation's most vulnerable workers.